Seagrass (Enhalus acoroides) as an Heavy Metal Bioindicator on Biomonitoring Water Quality in Sanur Beach Bali - Wijayanti, Ni Putu Putri; Giri Putra, I Nyoman (Advances in Tropical Biodiversity and Environmental Sciences; Vol 3 No 1 (2019): ATBESDO - 10.24843/ATBES.2019.v03.i01.p05, 2019)
Abstract. Heavy metal contamination is a major threat for marine ecosystem that directly affecting the organisms’ life. Some of marine organisms have an ability to response the heavy metal contamination in water, and could be used as bio-indicator. One of them is seagrass that used in this study to evaluate the water quality in Sanur beach. This study was held in Sanur beach, Denpasar, from July-August 2018. Sampling location determined by purposive sampling method and generated 4 research stations. Sediments and seagrass leaves ( Enhalus acoroides ) was collected and analyzed in Analytical Laboratory Udayana University using ICPE-9000. Water quality parameters measured in situ (temperature and salinity) and in Medical Laboratory Bali Province (pH and DO). The results showed if the water quality in all research stations were in safety range based on Governor Regulation No. 16 of 2016 about marine water quality for tourism and recreation. The highest content of heavy metal (Pb) in sediment is 16.207 mg kg -1 that possessed by the 1 st station, while the lowest is 14.318 mg kg -1 at the 3 rd station. The highest Pb content in seagrass leaves at the 2 nd station is 5.646 mg kg -1 , and the lowest at the 1 st station is 4.926 mg kg -1 . The 3 rd station sediment had the highest Cd content is 2.252 mg kg -1 and the 4 th station had the lowest is 2.044 mg kg -1 , while for leaves with the highest Cd content was at the 4 th station is 0.552 mg kg -1 and the lowest at the 3 rd station is 0.458 mg kg -1 . The Cu content in sediment was highest at the 1 st station is 11.533 mg kg -1 and the lowest at the 3 rd station is 8.501 mg kg -1 . For leaves’ Cu content, the highest amount of Cu is 3.699 mg kg -1 at the 4 th station, while the lowest at the 2 nd station with 2.570 mg kg -1 .